(untitled) (Boletín Epidemiológico Semanal, 2023)
Introduction: dengue is a human Aedes mosquito-borne disease, mainly imported in Spain. Due to Aedes albopictus presence, there is a risk for autochthonous transmission in our territory. The aim of the study was to analyse the information on dengue in Spain in 2022. Method: Epidemiologic descriptive analysis of dengue cases notified to the Spanish Surveillance System in 2022. Sociodemographic (age, sex, place of residence, autonomous region –AR– of notification), clinical (severity, hospitalization, dead, date of onset) and exposition (country and reason for travel) variables were analysed. Temporal trend from 2016 was described and notification rates (NR) by AR were calculated. Results: there were 503 notified cases, out of which 358 were confirmed and none autochthonous in Spanish residents. From 2016 to 2022 the maximum was in 2022 and 2019, and the minimum in 2020 and 2021. The higher NR corresponded to Catalonia (2,31), Navarra (2,12), Basque Country (1,88) and Madrid (1,51). Among cases, the majority were in summer, with maximum in August (33,3%). The most frequent place of infection was Latin America (82%), specially Cuba (66,4%) in tourism travellers. The 73% of viraemic cases were in AR with Ae. albopictus during its activity season. 30% of cases were admitted to hospital but there were no deaths. Conclusions: in 2022 the number of reported cases achieved the maximum since 2016, specially during summer season and in regions with vector presence, which determines the probability of local cases. The majority of cases were imported from Cuba, they were mild and evolved well.